Atribuição de prenomes de batismo: imigrantes alemães, identidade étnica e construção de um mundo simbólico (Curitiba, Brasil; 1866-1987) - Sergio Odilon Nadalin (Centre de Recherches sur les Mondes Américains, 2008)
This text sets out with the presupposition that people’s first names signal a symbolic consumption in present and past societies. In the same way, naming children ensues from a widespread social practice according to which a name represents a sign of both recognition and “belonging” (Gelis). In the case of a community composed of immigrants and their descendants, the symbolic character afore mentioned is also characteristic of differentiating cultural features in the scope of construction (and deconstruction) of an ethnic identity. In other words, in an ethnic group, choosing a name would express a specific signal or sign of cultural contacts, constituting diacritical features which people look for and exhibit to show their identity (Barth). Thus, our intention is to observe the means used by the members of a group organized as a Lutheran parish in an urban and multicultural space in order to achieve their integration into the receiving society. Based on the data from family records (Fleury/Henry) organized in four cohorts, our assumption is that there is a different kind of concern in relation to one’s ethnic identity depending on chronological period and order of births. In addition, the hypotheses elaborated here are based on the idea that “categories” of first names as signs of identity can help us understand the dynamics of ethnic frontiers built by the group.